6 - Devenir un(e) résident(e) privilégié(e) au Sénégal : migrations depuis l'Occident, ascensions sociales et subversions locales - Quashie, Hélène (African Sociological Review, 2023)
This paper analyses several parameters through which Westerners coming from Europe and North America acquire privileges due to their migration to Senegal. This includes people belonging to African diasporas. These privileges are quantified through administrative convenience, little control from the State, and detachment from various aspects in local everyday life, in which migrants from of the Global North do not include themselves. The analysis focuses on the building of Western microcosms, but also outlines their social and racial divisions, as well as values and resilience shaping local subversion and infrapolitics against